2009
DOI: 10.1097/acm.0b013e3181bb2d51
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Longitudinal Effects of an Embedded Specialty Curriculum on Physical Examination Skills Using an Ophthalmology Model

Abstract: Additional training successfully reinforced skills performance, which nonetheless decayed when not habitually practiced. Neither physical diagnosis preceptor ratings nor excellent performance in the FM ophthalmology module predicted subsequent skills performance in other clerkships or on simulator testing. The present study supports a reiterative retraining model for teaching this and other specialty physical examination skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…It is important to emphasize however that these scores derived from checklists items measuring only the exam technique and not detection and interpretation of the clinical signs found. Maintenance of these clinical skills is again most likely to be explained by continuous practice after the initial acquisition, since as, at least for skills related to the examination of the eye [21], additional training successfully reinforces performance, which progressively decays with non practice. Our findings, obtained in an educational scenario characterized by a richness of opportunities for practicing clinical skills, as already mentioned, are in accordance Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize however that these scores derived from checklists items measuring only the exam technique and not detection and interpretation of the clinical signs found. Maintenance of these clinical skills is again most likely to be explained by continuous practice after the initial acquisition, since as, at least for skills related to the examination of the eye [21], additional training successfully reinforces performance, which progressively decays with non practice. Our findings, obtained in an educational scenario characterized by a richness of opportunities for practicing clinical skills, as already mentioned, are in accordance Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the retention of physical examinations skills has only been investigated in very specific settings, such as eye examinations [21] and studies on more general skills are even more scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that proficiency with ocular fundus examination, as with many other skills, decreases without regular reinforcement. 12 Furthermore, there is evidence that most medical students are uncomfortable with direct ophthalmoscopy. 11 The preservation of the ocular fundus examination as a skill important to neurologists and primary care physicians will likely require creative solutions that (1) improve the diagnostic yield of ocular fundus examination, (2) reinforce the vital role of ocular fundus examination in patient care, and (3) increase enthusiasm for the ocular fundus examination that some may already view as a dying art.…”
Section: Ophthalmoscopy In Medical Student Educationmentioning
confidence: 99%
“…However, even the most innovative approach to teaching is unlikely to take full effect if only implemented once throughout a six-year curriculum. Repeated training reduces the rate at which skills are lost [22,23] but its implementation can be challenging given the growing body of information to be covered in undergraduate medical education. However, even ongoing training may not be sufficient unless coupled with appropriate exams.…”
Section: Implications For Teachingmentioning
confidence: 99%